Ensino remoto emergencial: análises das práticas pedagógicas de alfabetização e avaliação implementadas por docentes do 2º ano do E. F. de municípios cearenses - Lima, Nágila Rabelo de (2022)
In a pandemic scenario, due to the emergence of Covid-19, teachers needed to make use of Emergency Remote Teaching (ERT), in a quick way, a situation that lasted for approximately two years in Brazil. ERT, an unprecedented and historical situation in the country, encountered barriers to its implementation, while at the same time demanded from teachers the development of innovative pedagogical practices and/or adapted to the situation in which they found themselves. Thus, this research had as its main objective to analyze the implementation of Emergency Remote Teaching, as well as the innovative pedagogical practices of literacy and assessment developed by teachers of the 2nd year of Elementary School of municipalities in the state of Ceará, in the context of the Covid-19 pandemic. This is a field research, with a qualitative and quantitative approach, which used an electronic questionnaire as a data collection instrument applied to fifty-seven (57) teachers, belonging to ten (10) municipalities in Ceará, awarded in external evaluations. The results showed that the use of pedagogical resources belonging to Information and Communication Technologies - ICTs, such as videos, games, internet, applications, digital materials and educational websites were inserted in the teachers’ praxis, making them develop differentiated pedagogical practices to meet the specific demand from ERT, which required new ways of thinking and acting, promoting teacher reflection and research. Regarding the assessment of reading and writing, teachers used various instruments such as Google Forms, observation, video calls and production of audios, texts, among others. In general, although they faced challenges, the experience with Remote Learning was positive, from the perspective of most teachers, due to the possibility of improving training, especially in relation to technological learning, and the partnership with the students’ families. On the negative aspects, the teachers cited difficulties in adapting to Remote Teaching, the impairment in student learning and preference and/or confidence in face-to-face teaching for the quality of teaching. We recognize that the development of innovative pedagogical and evaluation practices, implemented by the research participants, was a possible reality, but we emphasize that the specificity of the literacy stage requires the need for the school environment, with all its possibilities, so that learning acquired during this period can be reassessed and incorporated into face-to-face teaching.